MODELLING AND SIMULATION OF COAL BIOSOLUBILIZATION KINETICS - Susilo, Kevin
Coal is one of the largest energy sources in Indonesia, but Indonesia’s coal reserves mostly consist of low rank coal with a low calorific value. Fakuossa (1981) showed that coal can be liquefied through biological process by microorganisms. The process is known as coal biosolubilization. Coal biosolubilization can potentially raise the value of low rank coal and increase the liquid fuel supply in Indonesia. However, no research on modelling of coal biosolubilization kinetics has been conducted until now. Kinetics modelling is a crucial step to design and develop coal biosolubilization research to a larger scale. This research aims to obtain kinetic models of coal biosolubilization through power law approach and simulate them in various initial coal concentration. The process is modelled using the previous research’s data conducted in Microbiology Laboratory, Chemical Engineering Department, Bandung Institute of Technology and Bioconversion Laboratory, Bioscience and Biotechnology Research Center, Bandung Institute of Technology. The constructed models are then used to simulate the effect of type of nitrogen sources, C/N ratio, medium phase, and initial coal concentration on coal biosolubilization. The kinetic models for coal to humic acid conversion give a positive value for reaction rate constants (kB) and order of reactions (m), while kinetic models for humic acid to fulvic acid conversion give a positive value for reaction rate constants (kF) and a negative value for the order of reactions (n). The simulation results show that ammonium nitrate is a better nitrogen source compared to ammonium sulfate with the best C/N is 15 for both nitrogen sources. Coal biosolubilization process perform better in solid state media than in submerge culture. The constructed models can be used to predict the rate of biosolubilization and concentration profile of coal, humic acid, and fulvic acid. However, the applicability of the models is limited to certain operating condition and cannot show the relation of other factors in coal biosolubilization.